SIMULATION-ASSISTED CHIMNEY DESIGN TO REDUCE ENERGY CONSUMPTION IN HEATING BOILERS IN BULANIK DISTRICT - Karahan, Ahmet; Balo, Figen (Muş Alparslan Üniversitesi, 2024)
Energy efficiency in boiler systems installed for heating purposes in buildings means both lower energy source consumption and reducing the amount of greenhouse gases that pollute the atmosphere released into the environment. Energy efficiency in boiler systems can be achieved with different applications. Some of these are the performance of the energy source used during the combustion process, i.e., whether the combustion occurs in the form of complete or incomplete combustion, correct burner and furnace design, increasing the amount of energy transferred to the fluid in the boiler after the combustion process, reducing the pollutants in the energy source used, and reducing flue gas emissions with correct chimney design. In this study, an energy-efficient chimney design was made for a three-story building designed in the climate conditions of Bulanık district of Muş province in case the heating need is met with a boiler system with a capacity of 125,000 kcal/h. Circular cross-section form was used as the chimney type and double-layer steel was used as the chimney design material. For a chimney design that will contribute to energy efficiency, the effects of different thicknesses (30 mm, 40 mm, 50 mm, 60 mm) of rock wool insulation material on operating parameters were investigated. In the case that the energy source for the boiler to which the chimney system is connected is natural gas, the effects on the amount of emissions released from the boiler chimney to the atmosphere were investigated. For this purpose, the German-origin KesaAladin simulation program was used. As a result of the analyses made with the KesaAladin simulation program, the emission values ??released to the environment were determined and the chimney design type with the lowest carbon emission and the lowest energy consumption was determined. The study results are intended to guide those involved in construction and chimney design in the district.

Binalarda ısıtma amacıyla kurulan kazan sistemlerinde enerji verimliliği, hem enerji kaynağı tüketiminin daha az olması hem de çevreye salınan atmosferi kirletici sera gazları miktarının azaltılması anlamına gelmektedir. Kazan sistemlerinde enerji verimliliği farklı uygulamalarla gerçekleştirilebilir. Bunlardan bazıları, kullanılan enerji kaynağının yanma olayı esnasındaki performansı, yani yanmanın tam ya da eksik yanma şeklinde gerçekleşmesi, doğru brülör ve ocak tasarımı, yanma olayı sonrasında ortaya çıkan enerjinin kazanın içerisindeki akışkana transfer miktarının artırılması, kullanılan enerji kaynağının içerisinde bulunan kirleticilerin azaltılması, ve doğru baca tasarımıyla baca gazı emisyonlarının azaltılmasıdır. Bu çalışmada, Muş ili Bulanık ilçesi iklim şartlarında tasarlanan üç katlı bir binanın 125 000 kcal/h kapasitesinde bir kazan sistemiyle ısınma ihtiyacının karşılanması durumunda bina için enerji etkin bir baca tasarımı yapılmıştır. Baca tipi olarak dairesel kesitli form ve baca tasarım malzemesi olarak çift katmanlı çelik kullanılmıştır. Enerji verimliliğine katkı sağlayacak bir baca tasarımı için farklı kalınlıklarda (30 mm, 40 mm, 50 mm, 60 mm) taş yünü yalıtım malzemesinin işletme parametrelerine etkileri araştırılmıştır. Baca sisteminin bağlı olduğu kazan için enerji kaynağının doğal gaz olması durumunda kazan bacasından atmosfere atılan emisyon miktarına olan etkileri araştırılmıştır. Bu amaçla Almanya menşeli KesaAladin simülasyon programı kullanılmıştır. KesaAladin simülasyon programı ile yapılan analizler sonucu çevreye salınan emisyon değerleri belirlenerek en düşük karbon salınımı ve en düşük enerji tüketimi içeren baca tasarım şekli belirlenmiştir. Çalışma sonuçlarının ilçede yapı ve baca tasarımıyla uğraşan ilgililere rehberlik etmesi amaçlanmıştır.
BULANIK İLÇESİNDE ISITMA KAZANLARINDAKİ ENERJİ TÜKETİMİNİ AZALTMAK İÇİN SİMÜLASYON DESTEKLİ BACA TASARIMI
Keywords: Turkish Economic Geography; Türkiye Ekonomik Coğrafyası